Skin nodules in a patient with acute lymphoblastic leukaemia. (9th January 2014) - Le Clech, Lenaïg; Hutin, Pascal; Le Gal, Solène; Guillerm, Gaëlle
Abstract : Opportunistic infections cause a significant morbidity and mortality in immunocompromised patients. We describe the case of a patient with skin fusariosis and a probable cerebral toxoplasmosis after UCB stem cell transplantation for B-cell acute lymphoblastic leukaemia. Fusarium species (spp) infections are difficult to treat. To date, there has been no consensus on the treatment of fusariosis and the management of its side effects. Given the negative pretransplant Toxoplasma serology in this case, identifying the origin of the Toxoplasma infection was challenging. All usual transmission routes were screened for and ruled out. The patient's positive outcome was not consistent with that of the literature reporting 60% mortality due to each infection.